By His Excellency William Livingston, Esquire ... proclamation : Whereas some of the justices of the peace of this state have been too remiss in discharging the duty required of them ... I have therefore thought fit ... to issue this proclamation, hereby strictly charging and commanding all justices of the peace within the same, to carry the said act into execution so far as to them it doth appertain. ... Given under my hand, and seal at arms at Haddonfield, the fifth day of February, in the year of our Lord one thousand seven hundred and seventy-seven (LLMC-digital (Series), 1777)
Charging all justices of the peace to carry out the prescribed punishments against British sympathizers.